CONTEXTUAL LEARNING MANAGEMENT TO IMPROVE STUDENTS’ SCIENCE COMPETENCE AT MADRASAH TSANAWIYAH IN BUNGO REGENCY - Mona Novita; Liana Wulandari (Epigram, 2025)
This study aims to analyze the management of contextual learning in improving students’ science competence at Madrasah Tsanawiyah in Bungo Regency. The research focuses on how the planning, implementation, and evaluation of contextual learning are organized to optimize students’ scientific understanding and engagement. The study employed a classroom action research design conducted in two cycles with 28 eighth-grade students as the subjects. Data were collected through observation, interviews, documentation, and achievement tests, and were analyzed using descriptive qualitative and quantitative methods. The findings reveal that contextual learning management through systematic planning, the use of real-world media, and reflective evaluation significantly improved students’ science competence. The percentage of students achieving the minimum mastery criterion increased from 25% in the pre-cycle to 85.71% in the second cycle. This improvement demonstrates that effective instructional management emphasizing student participation, collaborative learning, and authentic assessment creates a meaningful learning environment that strengthens both cognitive mastery and scientific skills. The study highlights that managing contextual learning with an integrative and reflective approach can serve as a strategic model for enhancing educational quality in Islamic junior high schools.